DASAR HUMANISME LOKAL INDONESIA - Jakob Sumardjo (Universitas PGRI Adi Buana Surabaya, 2014)
Pre-modern humans Indonesia is very respectful of nature which is a pair of human life. If youcut down a tree, picking rice, take honey, slaughtering animals, it is always preceded by a smallritual apology. To understand the local culture, it cannot be used the measures of modernity thatrejects the things metaphysical and supernatural things. Inevitably we have to be willing to leaveour modern rationality to understand other types of rationality that develops in the local culture of Indonesia. The realities for local cultures include things that are visible (empiricism) and invisible(hidden). Human being is in the nature both of them. The Local human pay attention more on thesupernatural than empirical, when the empirical is not able to solve their problems, at least there isa guarantee from supernatural power in solving the empirical ones. To realize the highest humangoal, people should become a perfect human being, and then every local knows the virtues of each.On the other hand, in fact, humans do not have any freedom which lies precisely in compliancein framed structures. When running what is in accordance with the concept structuralism, thenhumans really feel free, carefree, contented and happy, whatever happens, and surrender to the willof god. The main human always close and remember the Lord. He was gone just as a mere tool.For further explanation, in this study, it will discuss about National Unity, Concept of Almighty,Concept of Plurality, Relationships among the one with the Human life, the Almighty Patterns, andthe Concept of Freedom.Keywords: local human, supernatural, local culture.